Pengaruh Mutasi Kerja, Lingkungan Kerja, dan Motivasi Kerja Terhadap Produktivitas Kerja pada Karyawan PT. XYZ Kota Gresik - Mohammad Zakhi Firdaus; Maulidyah Amalina Rizqi (Populer: Jurnal Penelitian Mahasiswa, 2024)
Human Resource Management (HRM) plays a very crucial role in the structure of an organization or company to achieve the goals that have been set, organizations or companies are expected to be able to increase employee work productivity to maintain competitiveness in the midst of competition with competitors, several factors affect work productivity including job transfers, work environment, and work motivation. The purpose of this study was to determine whether job transfers, work environment, and work motivation affect work productivity. The method used in this study is a quantitative method with multiple linear regression analysis. Using 42 sample respondents of PT. XYZ employees in Gresik City. The regression results show that the job transfer variable (X1) has a positive and significant effect on the work productivity of PT. XYZ employees in Gresik City. The work environment variable (X2) has a negative and significant effect on the work productivity of PT. XYZ employees in Gresik City. The work motivation variable (X3) has a positive and significant effect on the work productivity of PT. XYZ employees in Gresik City.